Efficacy and Safety of Sugammadex to Shorten Time-to-Extubation Following Cardiac Surgery: A Single-Center Randomized Placebo-Controlled Trial. (22nd December 2022) - Bardia, Amit; Treggiari, Miriam M.; Dai, Feng; Johnson, Chanel; Singh, Manila; Kunze, Kim; Tickoo, Mayanka; Tantawy, Hossam; Giersson, Arnar; Darr, Umer; Schonberger, Robert B.
Abstract : OBJECTIVES: Residual neuromuscular blockade (NMB) is an important and modifiable factor associated with prolonged mechanical ventilation after cardiac surgery. Studies evaluating the use of sugammadex for residual NMB reversal in the post-cardiac surgery ICU setting are lacking. We conducted a randomized trial to determine the efficacy of sugammadex in reducing time to extubation in patients admitted to the ICU after cardiac surgery. DESIGN: Single-center, randomized, double-blind, placebo-controlled trial. SETTING: University-based cardiothoracic ICU. SUBJECTS: Patients ( n = 90) undergoing elective aortic valve replacement (AVR) and/or coronary artery bypass grafting (CABG) surgery. INTERVENTIONS: Participants were randomized to receive either sugammadex (2 mg/kg) or placebo after arrival to the ICU. MEASUREMENTS AND MAIN RESULTS: The primary study endpoint was time from study drug administration to extubation. Of the 90 patients included in the study (45 in each group), a total of 68 patients underwent CABG, 13 AVR, and nine combined AVR and CABG. Baseline characteristics and intraoperative anesthetic medications were comparable between groups. Patients in sugammadex group had reduced time to extubation compared with the placebo group (median [interquartile range (IQR)]—sugammadex group: 126.0 min [84.0–274.0 min] vs placebo: 219.0 min [121.0–323.0 min]; difference in means [95% CI], 72.8 [1.5-144.1 min]; p = 0.01. There were no differences in negative inspiratory force (mean [sd ]—sugammadex group: 33.79 cm H2 O [8.39 cm H2 O] vs placebo: –31.11 cm H2 O [7.17 cm H2 O]) and vital capacity (median [IQR]—sugammadex group: 1.1 L [0.9–1.3 L] vs placebo: 1.0 L [0.9–1.2 L]). There were no differences between groups in postoperative blood product requirement, dysrhythmias, length of ICU, or hospital stay. There were no serious adverse events in either group. CONCLUSIONS: This randomized trial showed that the administration of sugammadex after cardiac surgery decreased time to extubation by approximately 1 hour. Larger trials may be required to confirm these findings and determine the clinical implications.